Carbapenem-resistant Enterobacterales colonisation in a tertiary PICU, Cape Town, South Africa - Elri du Plooy; Angela Dramowski; Pieter Nel; Noor M. Parker; Helena Rabie (Southern African Journal of Infectious Diseases)
Background: Carbapenem-resistant Enterobacterales (CRE) are important healthcare-associated pathogens in resource-limited paediatric intensive care units (PICUs). The prevalence and clinical predictors of CRE colonisation in South African PICUs are unknown.